Konsep Pendidikan Rumah Tangga dalam Perspektif Cahyadi Takariawan - Ernawati, Ernawati (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Forming an ideal household requires spiritual mental, intellectual, and physical preparation to go through the life in order to achieve harmony of the family which aresakinah, mawaddah, warrahmah. Therefore, Islamic education in the household is very necessary, as it is stated in the works of Cahyadi Takariawan about applicative household. Problem of this research is, How is Islamic education concept in the household? How is household educational concept in the perspective of Cahyadi Takariawan? Is there any relevance between Islamic education in the household and Cahyadi persepectives in the modern era? This is a library research. The approach used is qualitative descriptive analysis. Primary data of this research is some works of Cahyadi Takariawan which have something to do with household. Secondary data is some other books which are relevant to the main problem. Data collection technique was done by using documentation. Meanwhile, data analysis was done by using descriptive analysis, content analysis, and symmetric association analysis.This research reveals three conclusions: Firstly, Islamic education concept in the household is dealing with meaning and scope of education, urgency of education, foundation of education, goal of education, and target of education. Secondly, household educational concept in the perspective of Cahyadi Takariawan related to meaning and scope of education, urgency of education, foundation of education, goal of education, and target of education. Thirdly, relevance between Islamic education in the household and Cahyadi perspectives in the modern era, they are pre marriage, marriage, and post marriage, harmonic couple, and samara family (sakinah mawaddah wa rahmah).